LABORATORY OF SCHOLARLY COMMUNICATIONS: RUSSIAN PERSPECTIVE - Elena M. Bazanova (Высшее образование в России)
The development of academic writing competence is an institutional responsibility of universities. To achieve this goal, most prestigious North American and European universities established writing centers where tutors, who have excellent academic writing skills and have been specially trained, help their fellow students improve their writing assignments. However, writing centers in Russian universities have proved to be true laboratories for scholarly communications as tasks they have to solve are conceptually different from those of overseas universities and the aims they attempt to reach are by far more challenging. One of such aims is to provide university researchers with expert help in order to develop their professional competencies so that they could significantly improve their publication outcomes and, as a consequence, succeed in the global academic community.